Dynamics of Harvest Subcontracting - Ortiz, Sutti (2012)
A historical perspective of three export agro-industries in Argentina (lemons, sweet citrus and tobacco) illustrates the range of factors that may foster subcontracting and the choice of subcontracting modalities. The case studies also illustrate that subcontracting is often a fragile strategy that leads to the eventual reabsorption of subcontracted tasks. We argue that the fragility of subcontracting the harvest rests on the inability of producers and labour contractors to negotiate a relationship that favours collaboration and problem solving. This failure is at the root of the high transaction costs of harvest subcontracting that force producers to resort to ancillary investments or sanctions, or to reabsorb some or all of the delegated tasks. A mismatch of resources and technical competence between producers and harvest labour contractors also contributes to inadequate performance of services. It is thus not surprising that harvest labour contractors are not always permanent fixtures; they may appear, disappear and reappear, particularly in fresh fruit export industries.